Boiling flow patterns and dry-out characteristics of R-1234ze(E) in a plate heat exchanger. (November 2020) - Lee, DongChan; Jo, ChangUk; Kim, Byeongsu; Kim, Yongchan
Highlights: Boiling flow patterns of R-1234ze(E) in a PHE are analyzed through visualization. Distinct flow boiling mechanisms at different regions in the PHE are reported. A flow pattern map in the PHE along with criteria for transitions is proposed. Dry-out characteristics in the PHE owing to the lack of liquid phase are studied. ABSTRACT: In this study, boiling flow patterns and dry-out characteristics of R-1234ze(E) in a plate heat exchanger (PHE) are investigated through visualizations and surface temperature measurements. The boiling flow patterns in the PHE are classified into three regimes by reflecting an evident flow direction and intermittent flooding (IF): rough liquid film flow, pulsating annular flow, and steady annular flow. Boiling mechanisms in the liquid-preferred and vapor-preferred paths are analyzed in a single channel. A boiling flow pattern map of R-1234ze(E) in the PHE is developed in terms of liquid and vapor superficial momentums, and the criteria for the transitions of the flow regimes are proposed to provide a reference for predicting flow characteristics during phase changes. Based on the measured surface temperatures, the partial dry-out is observed at medium to high vapor qualities in the center of the vapor-preferred path owing to the lack of the liquid phase. In addition, the relationships between the IF, partial dry-out, and heat transfer coefficients are comprehensively analyzed with physical interpretations.